2019
DOI: 10.1186/s10020-019-0104-3
|View full text |Cite
|
Sign up to set email alerts
|

FOXD1 mutations are related to repeated implantation failure, intra-uterine growth restriction and preeclampsia

Abstract: Background Human reproductive disorders consist of frequently occurring dysfunctions including a broad range of phenotypes affecting fertility and women’s health during pregnancy. Several female-related diseases have been associated with hypofertility/infertility phenotypes, such as recurrent pregnancy loss (RPL). Other occurring diseases may be life-threatening for the mother and foetus, such as preeclampsia (PE) and intra-uterine growth restriction (IUGR). FOXD1 was defined as a major molecule i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…The mechanisms of the relationships found (between smoking in the first trimester and the risk of birth weight <10th percentile, LBW, and FGR) are not fully understood. The main factors affecting fetal growth include the placenta, which guarantees the flow of nutrients to the fetus [14][15][16]. Factors causing hypoxia and reductions of blood flow in the placenta may increase the risk of FGR, SGA, and LBW [2,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms of the relationships found (between smoking in the first trimester and the risk of birth weight <10th percentile, LBW, and FGR) are not fully understood. The main factors affecting fetal growth include the placenta, which guarantees the flow of nutrients to the fetus [14][15][16]. Factors causing hypoxia and reductions of blood flow in the placenta may increase the risk of FGR, SGA, and LBW [2,7].…”
Section: Discussionmentioning
confidence: 99%
“…Fetal growth restriction (FGR) was diagnosed based on ultrasound in pregnancy (all cases were recorded, regardless of phenotype) [14][15][16]. FGR was defined as the fetus' inability to reach its full growth potential and was diagnosed based on ultrasound in pregnancy.…”
Section: Definitions Of Dependent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that creating gene subsets from WES for studying unrelated patients on a large genomic scale is a powerful strategy for identifying new genes and mutations related to complex polygenic phenotypes. [19][20][21][22] Three subsets (AE, PH and TF) were created in this study, forming the starting point for filtering candidate sequence variants regarding different genomic and pathophysiology hypotheses. We consider that the PH category contains a comprehensive collection of genes that have been well-documented concerning drug metabolism, some of which are available for commercial/diagnostic purposes (eg, ABCB1, CYP1A2, CYP2B6, CYP2C8, CYP2C9, CYP2D6, CYP3A4, UGT1A1, SLC47A2, D2 and HTR2A).…”
Section: Wes Gene Subset Analysis: An Innovative Genomic Approach Formentioning
confidence: 99%
“…A previous study using this methodology identified FOXD1 as a major gene involved in the regulation of embryo implantation in mice and various reproductive disorders in humans. 20,25 Variant filtering assumed that rare (MAF <1%) nonsynonymous variants in AE, PH and/or TF subsets (underlining potential moderate/drastic functional effects) might contribute towards the origin of SJS-TEN. Indeed, it has been demonstrated that using NGS for studying extreme phenotypes facilitates mapping rare sequence variants contributing to complex traits' origins.…”
Section: Wes Gene Subset Analysis: An Innovative Genomic Approach Formentioning
confidence: 99%